Advanced Electrical Conductors: An Overview and Prospects of Metal Nanocomposite and Nanocarbon Based Conductors. Issue 8 (8th March 2021) - Tehrani, Mehran
Abstract : Advanced electrical conductors that outperform copper and aluminum can revolutionize our lives by enabling billions of dollars in energy savings and facilitating a transition to an electric mobility future. Nanocarbons (carbon nanotubes and graphene) present a unique opportunity for developing advanced conductors for electrical power, communications, electronics, and electric machines for the defense, energy, and automotive industries. Herein, the major research progress in the field of advanced nanocarbon‐based and metal–nanocarbon conductors is compiled. The benefits and drawbacks of advanced conductors are also elucidated with respect to conventional ones and their materials science, mechanical and physical properties, and characterization are discussed. Finally, several areas of future research for advanced electrical conductors are proposed. Abstract : Advanced electrical conductors (based on nanocarbons or their metal nanocomposites) that outperform copper and aluminum can save billions of dollars in electricity bills and facilitate an electric mobility future. This article presents the state of the art in advanced conductors, proposes new directions for their future research, and intends to educate diverse researchers on the fundamentals of advanced conductors.